2017
DOI: 10.2174/1745017901713010156
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Depression, Burnout and Low Quality of Life Among Personnel of a University Hospital in Italy is a Consequence of the Impact One Economic Crisis in the Welfare System?

Abstract: Background:Research literature suggests that burnout, depression, and a low mental quality of life (QOL) are common among health care workers. Economic crisis might have increased the burden of burnout, depression and low QOL in health care workers.Objectives:To identify depression risk, burnout levels, and quality of life in a sample of workers of an Italian university hospital.Method:Cross sectional study with comparison with two community surveys database results (n = 2000 and 1500, respectively). Overall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
2
19
1
1
Order By: Relevance
“…The high prevalence of depression, anxiety, and burnout is a major concern for physicians' well-being and career progress. Several studies have suggested that depression and burnout can carry further risk, progressing chronically throughout a physician's life ( 51 53 ). It should also be emphasized that psychological distress and mental fatigue can affect a person's work performance, increasing the risk of medical error, which not only affects physicians but also has adverse effects on the quality of care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of depression, anxiety, and burnout is a major concern for physicians' well-being and career progress. Several studies have suggested that depression and burnout can carry further risk, progressing chronically throughout a physician's life ( 51 53 ). It should also be emphasized that psychological distress and mental fatigue can affect a person's work performance, increasing the risk of medical error, which not only affects physicians but also has adverse effects on the quality of care for patients.…”
Section: Discussionmentioning
confidence: 99%
“…To begin with, the patient is a healthcare professional and thus part of a professional group under enormous social and mental strain due to the pandemic. Being part of a professional group that in a health emergency has the duty to care for ill people and is therefore responsible for public well-being is likely to generate stress and stress-related clinical manifestations [ 29 , 30 ]. In light of the above-mentioned points, we cannot exclude the possibility that the patient’s psychological stress could have had an influence on the subjective perception of pruritus, worsening it.…”
Section: Discussionmentioning
confidence: 99%
“…Zdravstvena struka, s obzirom na visoku odgovornost prema ljudskom životu i zdravlju, ali i zbog izloženosti specifičnim stresorima, poput hemijskih, bioloških i fizičkih štetnosti i smenskom radu, svrstava se u visoko stresne profesije. Produženo radno vreme, smenski i noćni rad, odgovornost pri donošenju odluka, kontakt sa obolelima i njihovim porodicama i emocionalno iscrpljivanje kod zdravstvenih radnika, utiču na povećan morbiditet od psihičkih smetnji i psihosomatskih bolesti (Carta et al, 2017;Lazaridis i sar., 2017). Određene grupe zanimanja u zdravstvenom sektoru kao na primer lekari različitih specijalnosti (hirurzi, lekari hitne pomoći, onkolozi, radiolozi, lekari u palijativnoj medicini, psihijatri) i medicinske sestre svih profila su hronično izloženi različitim stresorima koji utiču na povećanje povređivanja na radu i smanjenu radnu sposobnost zbog profesionalnog stresa i oboljevanja (Andolhe et al, 2015;Wang et al, 2015).…”
Section: Stres I Profesionalni Stresunclassified